A practical shear wall layout optimization framework for the design of high-rise buildings. (December 2021) - Lou, H.P.; Ye, J.; Jin, F.L.; Gao, B.Q.; Wan, Y.Y.; Quan, G.
Abstract: In the design of high-rise buildings, the lateral structural system that resists seismic and wind actions often dominates the overall design, and as a result, the optimum design of the lateral structural system is important for material efficiency. This paper aims to present a new design methodology that relies on an extended Evolutionary Structural Optimization (ESO) method to optimize the shear wall layout for the design of high-rise buildings. By discretizing all the shear walls of the ground structure into wall elements, different shear wall layouts were described by a binary matrix where '0′ and '1′ indicate the absence or presence of a wall element respectively. The proposed framework borrowed the intuitive concept of the ESO method, where the less stressed wall elements in the structure were gradually removed but the highly stressed wall elements were reserved. The conceptual design method was combined with the optimization algorithm to control the optimization process and to reduce structural eccentricity considering architecture, strength and serviceability constraints. Then, the structural weight could be automatically minimized under multiple loading cases and design constraints. By integrating the commercially available ETABS, a dedicated optimization software with an independent interface was developed and details were also presented in this paper for practical software development. The proposed framework was used to optimize the layouts of different shear wall structures, and case studies showed that the proposed framework could optimize shear wall structures with a material saving of up to 14% compared to the conventional design, which proved the feasibility and effectiveness of the framework. The paper can therefore be referenced by other researchers and software engineers to further explore the layout optimization of shear wall structures and to reduce material usage for a more sustainable design.